Exploring the role of genetic markers in disease progression and patient response to treatment - Bharti Sao, Rupali; Chandrakar, Kunal (Journal of Neonatal Surgery, 2025)
One of the most important areas of research in contemporary medicine is the understanding of how genetic markers affect the course of disease and the response of patients to treatment. The impact of particular genetic variations on the course of different diseases is examined in this work, with an emphasis on how well they can forecast disease outcomes and direct treatment choices. Through the analysis of genetic data from patient cohorts across various disease types, such as autoimmune disorders, cardiovascular diseases, and cancer, the study finds important markers linked to suboptimal treatment responses and faster disease progression. The study also addresses the possibility of using these genetic markers to inform personalized medicine strategies, highlighting the necessity of tailored treatments that take a patient's genetic profile into account.